Pescape: A tool developed to record environmental crimes in fishing in Pernambuco (Research, Society and Development, 2024)
The article addresses the development of the Pescape platform, a tool for recording environmental crimes in fishing in Pernambuco, and the serious threat of environmental crimes in fishing, highlighting the economic and cultural importance of the activity. Crimes such as overfishing, the use of illegal equipment, and fishing in protected areas are identified as causing serious environmental impacts, compromising marine biodiversity. The lack of reliable information and a platform for recording and monitoring these crimes hinders the effectiveness of preventive measures. Law No. 15,590 of 2015 is cited as legal support that emphasizes the importance of promoting technological innovations in artisanal fishing. In this context, five fundamental objectives guide the project, aiming for the efficient development of the tool, increased transparency, facilitation of decision-making, reduction of environmental crimes, and contribution to the preservation of ecosystems. In the end, a usability test is applied: the analysis underscores the ongoing importance of usability in the evolution of the tool. In summary, Pescape seeks to be an effective solution for the preservation of marine ecosystems, providing an accessible and intuitive tool for recording and combating environmental crimes in fishing in Pernambuco.